Lower glycemia levels in subjects with excessive erythrocytosis during the oral glucose tolerance test living in conditions of severe hypoxia - Vilca Coaquira, Kely Melina; Rojas Chambilla, Rossela Alejandra; Tejada Flores, Jeancarlo; Tintaya Ramos, Henry Oscar; Quispe Trujillo, Mariela Mercedes; Quispe Humpiri, Solanyela Anny; Calisaya Huacasi, Ángel Gabriel; Pino Vanegas, Yony M.; Peña Vicuña, Gilberto Félix; Salazar Granara, Alberto Alcibiades; Tacuna Calderon, Ana Lucia; Garcia Bedoya, Nancy Monica; et al. (Frontiers in Physiology, 2024)
Background: Previous studies showed that residents of higher elevations have lower glucose levels. Our objective in this current study is to determine the basal and postprandial glucose levels in apparently healthy permanent residents of the miner population center of La Rinconada located 5100 meters (m) above sea level. Method: Forty male permanent residents of the Rinconada minor population center were studied. The oral glucose tolerance test was used to evaluate basal and postprandial glycemia levels at 1, 2 and 3 hours. The individuals had a mean age of 42.47 years + 8.04 SD. Basal glycemia in subjects without excessive erythrocytosis (EE) was 73.11 mg/dL + 7.81 SD while levels in patients with EE was 57.98 mg/dL +7.38 SD. In the postprandial period, at 1 hour after oral glucose overload a mean value of 76.35 mg/dL + 13.53 SD was observed in subjects with EE compared to 94.68 mg/dL + 9.98 SD in subjects without EE. After 2 hours, subjects with EE had a glycemia level of 72.91 mg/dL + 9.17 SD EE compared to 90.73 mg/dL + 13.86 SD without EE. At 3 hours, the average glycemia level in subjects with EE was 70.77 mg/dL + 8.73 SD compared to 87.79 mg/dL + 14.16 SD in those without EE. These findings suggest that under hypoxic conditions, glycemia levels are lower in both subjects with and without EE, having obtained lower levels in subjects with EE in relation to those with normal values of Hb and Hct. The results of this study indicate that in the conditions of severe hypoxia, blood glucose levels are below the values considered normal for sea level.